Obesity is a Threat to Our School Going Children - Amjad, Mohammad; Zafar, Muhammad Iqbal; Maan, Ashfaq Ahmed; Ali, Shoukat (Pakistan Journal of Nutrition, 2015)
Obesity is an increased and undesirable fat accumulated in a body. Overweight is high body weight in comparison with height while keeping in mind the desirable weight as per age. The study was conducted in two districts of Punjab namely Faisalabad and Rawalpindi. Total 12 schools were selected, randomly, from each district considering the area i.e. Posh Private, Public and Rural schools. Thus total 24 schools were considered for the study. Respondents were male students from grade 5 to 9 in each school. Total sample size was 600 children, 300 respondents from Faisalabad and 300 respondents from Rawalpindi district. A sample of 25 respondents was carefully selected from each school to make a total sample size of 600. The data was collected through a well-structured and pre-tested interviewing schedule. The height and weight of each respondent was measured using calibrated scales. Body Mass Index (BMI = weight [(kg)/height2 (m2)] was calculated for each student. The obtained data then was analyzed by using descriptive statistics, bivariate analysis and multivariate to find the relative significance of independent variables in explaining dependent variable. Results show that obesity of the children was significantly affected by family types, family size, family history, TV watching, internet use, sports and exercise hours, use mutton and beef, junk food, mother’s education, family size, weekly time spent in walking and playing facility at school in Punjab. Obesity affects respondents’ academic performance, physical health and psychological health, both in rural and urban areas.